2022
DOI: 10.1002/we.2788
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of power performances and flow characteristics for a Savonius rotor by vortex particle method

Abstract: This study investigates the implementation of the vortex particle method (VPM) with the goal of efficiently and accurately estimating the power performances and flow characteristics for a Savonius rotor. The accuracy and efficiency of simulation methods are critical for the reliable design of Savonius rotors. Among various approaches, VPM is chosen because it can be flexibly incorporated with selfcorrection techniques, and the distribution of bound vortex particles can effectively represent complex geometries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The advantage of using wind turbines with a vertical axis of rotation is the generation of electricity due to the possibility of self-starting and the absence of dependence on the wind direction on the example of the Savonius rotor [13]. But these installations have a disadvantage in the form of low efficiency, and the negative torque generated on the return blade limits its use in a large mastshab.…”
Section: Discussion Of the Results Of The Study Of The Aerodynamic Ch...mentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of using wind turbines with a vertical axis of rotation is the generation of electricity due to the possibility of self-starting and the absence of dependence on the wind direction on the example of the Savonius rotor [13]. But these installations have a disadvantage in the form of low efficiency, and the negative torque generated on the return blade limits its use in a large mastshab.…”
Section: Discussion Of the Results Of The Study Of The Aerodynamic Ch...mentioning
confidence: 99%
“…Article [13] presents the results of a numerical study of the energy and flow characteristics for a Savonius rotor using the vortex particle method (DTVPM). It is shown that DTVPM makes it possible to effectively model the Savonius rotor without any empirical parameters.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Jin et al 16 investigated 2D unsteady flows around polygons using a vortex method. Pan et al 17 implemented the vortex particle method to simulate transient blade forces and wake fields around the turbine. The kinematic models are quite complex due to the necessity of solving the unsteadiness of flow.…”
Section: Introductionmentioning
confidence: 99%